Gingival state and presence of red complex bacteria in 12-year-old schoolchildren = Estado gingival y presencia de bacterias del complejo rojo en escolares de 12 años - Vega Chin, Alberto 1991-
The objective of this study was to determine the gingival state and presence of red complex bacteria in saliva samples of 12-year-old schoolchildren. A calibrated periodontist evaluated biofilm index (BI) (Silness and Löe, 1964), presence of calculus, and gingival index (GI) (Silness and Löe, 1967) in sixty two 12-year-old students of Carmen Lyra School. Saliva samples were collected from each student. The DNA of each sample was extracted and amplified by the polymerase chain reaction (PCR) technique, using specific primers. The BI was 1.18. Calculus was present in 40.40% of the schoolchildren examined; 19.4% was supragingival calculus and 21% both supragingival and subgingival calculus. The GI was 0.97, which according to Silness and Löe is mild gingivitis. Gingivitis was present in 96.8% of the children examined. Regarding the PCR tests: 18 of the samples (31.58%) did not present any of the bacteria analyzed and the remaining 39 samples (68.42%) were positive for at least the presence of red complex bacteria. Within the limitations of this study, it is concluded that the prevalence of gingivitis and calculus is high in the sample examined, and the gingival state observed in the study population, may be related to the presence of red complex bacteria.